Successful use of a topical mixture with ozolipoile in the treatment of actinic ulcers - Inchingolo F; Tarullo A; Cagiano R; Resta G; Dipalma G; Inchingolo AM; Tarullo A; Scacco S; Marrelli M; Corti L; Tatullo M (Dove Medical Press, 2015)
Francesco Inchingolo,1 Angelo Tarullo,2 Raffaele Cagiano,2 Gianpiero Resta,3 Gianna Dipalma,3 Angelo Michele Inchingolo,3 Antonella Tarullo,3 Salvatore Scacco,4 Massimo Marrelli,5,6,* Luigi Corti,7,* Marco Tatullo8,* 1Department of Interdisciplinary Medicine, University of Bari “Aldo Moro”, Bari, 2Department of Biomedical Sciences and Human Oncology, University of Bari “Aldo Moro”, Bari, 3Private Practice, Dental Clinic, Bari, 4Department of Basic Medical Sciences, Neurosciences and Sensorial Organs, University of Bari “Aldo Moro”, Bari, 5Maxillofacial Unit, Calabrodental Clinic, Crotone, 6Healthcare Center, Marrelli Hospital, Crotone, 7UOC of Radiotherapy and Nuclear Medicine IOV – IRCCS, University of Padova, Padova, 8Biomedical Section, Tecnologica Research Institute, Crotone, Italy *These authors equally contributed to this research paper Purpose: Post-radiation skin damage is the result of alterations produced in the irradiated zone. There are different studies aimed at verifying the effectiveness of several kinds of molecules in the treatment of radiation-induced skin damage. The purpose of this study is to test a mixture with a formulation containing several natural active ingredients on actinic ulcers in patients receiving radiation therapies. Patients and methods: The authors recruited 13 patients, and randomly divided them into a test group (T1) and a control group (T2). The patients in both groups were undergoing radiotherapy. The T1 group was treated with a mixture called ozolipoile, whereas the T2 group was administered hyaluronic acid gel followed by non-ablative laser therapy. We evaluated the obtained results, the time of clinical healing, the reduction of pain, and each side effect, comparing all data between the T1 and T2 groups. Results: The average Visual Analog Scale results showed decrease in pain in both groups; however, while the T1 group showed a significant decrease in the values, the T2 group reported a more gradual reduction in the values, without ever reaching the minimum values obtained with the treatment with ozolipoile. Conclusion: Treatment of actinic ulcers with ozolipoile mixture leads to faster control of pain and to better healing of small-size ulcers. Keywords: actinic ulcers, radiation-induced ulcers, skin wound, ozonide, wound healing